Increasing e-government adoption by emphasizing environmental sustainability: an extended case study in Peru - Pérez Chacón, Sebastián Ramón (2021)
Purpose: Low citizen adoption rates jeopardize the success and proliferation of e-government systems. This study aims to understand how the perception of environmental sustainability (ES) can influence a citizen’s intention to use e-government systems. Design/methodology/approach: In a case study in Peru, the technology acceptance model (TAM) adoption model is extended with the construct of ES and evaluated with structural equation modeling. An 18-element, in-person survey was constructed and administered to citizens of Lima, Peru who had prior exposure to e-government systems. Findings: The results show that citizens can be positively influenced to adopt e-government systems if they perceive that doing so will contribute to ES. Research limitations/implications: As this was a preliminary study, further research should focus on specific, as opposed to general, e-government systems, as well as encompassing a broader cross section of the population. Practical implications: Administrators of e-government initiatives can consider public-interest factors, alongside of the common self-interest factors, when looking to improve adoption rates of e-government systems. Originality/value: This is the first time that TAM has been extended with the construct of ES.